Evaluation of the Antioxidant Activity and Antiproliferative Effect of the Jaboticaba (Myrciaria cauliflora) Seed Extracts in Oral Carcinoma Cells. (18th August 2014) - Wang, Wen-Hung; Tyan, Yu-Chang; Chen, Zong-Shiow; Lin, Ching-Gong; Yang, Ming-Hui; Yuan, Shyng-Shiou; Tsai, Wan-Chi
Abstract : It is becoming increasingly evident that certain phytochemicals possess cancer chemopreventive properties. In this study, the antiproliferative activity of extracts from different parts of the jaboticaba ( Myrciaria cauliflora ) plant was evaluated for its effect on human oral carcinoma cell lines. The cytotoxicities of various plant extract concentrations were examined and the 50% maximal inhibitory concentration (IC50 ) was determined. Water extracts of jaboticaba seeds showed concentration-dependent antiproliferative effects. Annexin V/propidium iodide positivity with active caspase-3 induction indicated that the treated cells underwent apoptosis. Several important regulatory proteins (Bcl-2, Bcl-xL, Bid, and survivin) involved in apoptosis were also evaluated. The antioxidant activity of jaboticaba was investigated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays, and the drug concentration eliciting 50% maximum stimulation (SC50 ) was determined. The present findings suggest that water extracts of jaboticaba seeds exhibit an antiproliferative effect against oral cancer cells by inducing apoptosis through downregulating survivin expression and thereby activating caspase-mediated Bid cleavage.